Assessment of stigma related to visible skin diseases: a systematic review and evaluation of patient‐reported outcome measures. (21st December 2021) - Luck‐Sikorski, C.; Roßmann, P.; Topp, J.; Augustin, M.; Sommer, R.; Weinberger, N.A.
Abstract: Misconceptions about visible skin diseases are widespread, and patients often face discrimination and stigmatization due to their condition. The associated negative health and psychosocial consequences of stigmatization in skin diseases have prompted an increase in research activity in recent times, resulting in a wide variety of assessment measures. This study aimed at aggregating and evaluating evidence of psychometric properties and methodological quality of published measures to assess stigma in visible skin diseases. Studies assessing stigmatization in visible skin diseases were searched in four databases (Medline, PsycINFO, Web of Science and Embase) until February 2021. The review followed PRISMA guidelines. Papers regarding development and/or validation of measures were identified by two independent researchers. Inclusion criteria were defined as follows: (i) quantitative studies in (ii) populations with skin diseases using (iii) questionnaires explicitly assessing (iv) perceived or public stigmatization or discrimination available in (iv) English or German language. The COnsensus‐based Standards of health Measurement INstruments (COSMIN) checklist was used to evaluate their psychometric properties and risk of bias. 35 studies using 21 instruments were identified. Twenty instruments focused on assessing the perceived reality of those affected by visible skin diseases, while public stigma was only assessed by two instruments. Twelve scales could be recommended for use, while nine instruments had the potential to be recommended after further studies have assessed their quality. Some limitations are to be noted. Only studies in English and German were included. Research on self‐constructed instruments can lead to new validated instruments, but they were not included in the review at this point. Several validated instruments could be recommended for use. Future research is needed regarding the assessment of stigma across different visible skin diseases, in children and adolescents, and in the general public.